PENGARUH MODEL PEMBELANJARAN CONCEPTUAL UNDERSTANDING PROCEDURES (CUPs) DENGAN ALAT PERAGA PAPAN DIAGRAM TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Nisa Anisa; Usep Saepul Mustakim; Ismi Widyaningrum (Cakrawala Pedagogik, 2026)
Abstract This study aims to examine the effect of applying the Conceptual Understanding Procedures (CUPs) learning model using diagram board visual aids on students’ mathematical concept comprehension. The research focuses on data presentation and involves seventh-grade students of SMPN 1 Cikedal as experimental and kontrol groups, each consisting of 24 participants. A quantitative approach was employed, with purposive sampling based on research objectives. The study adopts a quasi-experimental design using a nonequivalent kontrol group. Data were collected through two tests administered to students pretest and posttest using five essay-based items that address indicators of mathematical conceptual understanding. Data analysis was conducted using a one-tailed test, showing that students taught using the CUPs model with diagram boards scored an average of 15.42 with a standard deviation of 3.092, while those taught through direct instruction scored an average of 12.53 with a standard deviation of 2.734. Based on one-tailed t-test analysis, the results yielded a t-value of 3.42, exceeding the critical value of 2.01 at a 0.05 significance level, thus rejecting H? and accepting H?. These findings indicate that the application of the CUPs model with diagram board visual aids significantly enhances students’ comprehension of mathematical concepts at SMPN 1 Cikedal during the 2024/2025 academic year. Keywords : Conceptual Understanding Procedures (CUPs), visual aids, mathematical concept comprehension.